Support network to the mastectomized woman - Inajara Mirapalhete Canieles; Rosani Manfrin Muniz; Ana Cândida Lopes Corrêa; Sonia Maria Könzgen Meincke; Lenícia Cruz Soares (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210790 Aim: to identify the support network to the mastectomized women. Methodology: qualitative, exploratory and descriptive. Conducted with five participants mastectomized support group for women with breast cancer "Mama Vida" in the city of Pelotas, Rio Grande do Sul. Results: this study has highlighted the family, friends, religion and the group "Mama Vida" as a support network. It has contributed to face cancer in an easier way and Faith is seen as a great responsible for healing and overcoming. Conclusion: this network was of relevance to that the women survive to all the alterations caused by the fact of "being" with breast cancer.